2006
DOI: 10.1038/sj.ijo.0803294
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium regulates ROS production in aP2-agouti transgenic mice on high-fat/high-sucrose diets

Abstract: Objective: We have previously demonstrated that 1a, 25(OH) 2 D 3 promotes adipocyte reactive oxygen species (ROS) production. We have now evaluated whether decreasing 1a, 25(OH) 2 D 3 levels by increasing dietary calcium will decrease oxidative stress in vivo. Methods: We fed low-calcium (0.4% Ca) and high-calcium (1.2% Ca from CaCO 3 ) obesity-promoting (high sucrose/high fat) diets to aP2-agouti transgenic mice and assessed regulation of ROS production in adipose tissue and skeletal muscle. Results: Mice on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
7
37
2
Order By: Relevance
“…Consistent with these observations, data from the present study indicate that calcitriol may increase multiple inflammatory cytokine and decreased anti-inflammatory cytokine transcription. In addition, data from the present study suggest that calcitriol also favors cytoplasmic oxidative stress by increasing NADPH oxidase expression, and our previous data demonstrate a regulatory effect of calcitriol on NAPDH oxidase expression [9] . However, this effect was absent with the combination of calcitriol with cortisone; attenuation of this effect by cortisone may contribute to the anti-inflammatory function of glucocorticoid.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Consistent with these observations, data from the present study indicate that calcitriol may increase multiple inflammatory cytokine and decreased anti-inflammatory cytokine transcription. In addition, data from the present study suggest that calcitriol also favors cytoplasmic oxidative stress by increasing NADPH oxidase expression, and our previous data demonstrate a regulatory effect of calcitriol on NAPDH oxidase expression [9] . However, this effect was absent with the combination of calcitriol with cortisone; attenuation of this effect by cortisone may contribute to the anti-inflammatory function of glucocorticoid.…”
Section: Discussionmentioning
confidence: 63%
“…Although the mechanism responsible for the development of systemic inflammation is not clear, multiple previous studies indicated that increased oxidative stress in accumulated fat is an underlying cause of dysregulation of adipocytokines [34][35][36][37] . We have shown previously that calcitriol was associated with oxidative stress and inflammation and stimulated the expression of multiple inflammatory cytokines in human adipocytes, while suppression of calcitriol by dietary calcium suppressed ROS and inflammatory cytokines independent of its anti-obesity effects [9] . Consistent with these observations, data from the present study indicate that calcitriol may increase multiple inflammatory cytokine and decreased anti-inflammatory cytokine transcription.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations